Konflik Pengelolaan Pos Kesehatan Nagari (POSKESRI) di Nagari Kudo-Kudo Inderapura Kabupaten Pesisir Selatan - Mayasari, Ela; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study aims to determine the dynamics of conflict, namely to find out how the pre-conflict, confrontation, crisis or peak of conflict and post-conflict are. Qualitative research with descriptive methods. Data sources, namely primary and secondary. Collecting data using observation, interviews and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The results of the study show that: 1) Pre-conflict, Poskesri is no longer operating as usual, because the village midwife who usually works at the Poskesri is no longer on duty. 2) Confrontation, at this stage where the conflict begins to open. The village midwife is no longer on duty at the Poskesri in Nagari Kudo-kudo Inderapura, basically the Nagari has proposed a replacement midwife but has not received a response. 3) Crisis or peak conflict, where problems start to peak and if communication is carried out, they will tend to accuse each other. The owner of the land that had been granted a grant for the establishment of the poskesri did not allow other midwives to fill the vacancy in the poskesri except from their relatives, while the village midwife's honorarium was also no longer coming down from the district government. 4) Post-conflict, this stage is from solving problems so that they become more normal. The nagari and nagari institutions have contributed and provided solutions because the nagari wants the best for its people. However, the solution has not been found so that Poskesri has not been operating until now.